PEL 2020
DOI: 10.7764/pel.57.2.2020.5
|View full text |Cite
|
Sign up to set email alerts
|

Diferencias de género en el conocimiento y las percepciones del cambio climático entre adolescentes. Metaanálisis

Abstract: ¿Existen diferencias de conocimiento acerca del cambio climático entre adolescentes mujeres yhombres? ¿Cómo perciben los adolescentes la crisis climática en función del género? Con el finde dar respuesta a estas preguntas se realizó un metaanálisis con una muestra de 84 artículosinternacionales seleccionados con la metodología de revisión bibliográfica sistematizada,para lo cual se identificaron aquellos en los que —de acuerdo con la variable de género—existían diferencias de conocimiento, percepciones y/o val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 0 publications
1
6
0
11
Order By: Relevance
“…PhD and male students show a low level of awareness of the need to reduce meat consumption, thus stressing the importance of education for climate emergency and climate literacy in Universities, which is crucial to achieve sustainable consumption patterns. When implementing policies based on a sustainable and healthy diet, policy makers should consider the gender differences observed in this and other studies such as García-Vinuesa et al [45]. It should be considered the higher awareness of female students to adopt less-meat diets in future approaches.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…PhD and male students show a low level of awareness of the need to reduce meat consumption, thus stressing the importance of education for climate emergency and climate literacy in Universities, which is crucial to achieve sustainable consumption patterns. When implementing policies based on a sustainable and healthy diet, policy makers should consider the gender differences observed in this and other studies such as García-Vinuesa et al [45]. It should be considered the higher awareness of female students to adopt less-meat diets in future approaches.…”
Section: Discussionmentioning
confidence: 78%
“…Also studies in Belgium have shown that females are more likely to reduce this consumption because of consequences to the environment and express greater support for animal rights and welfare [44] (Figure 11) and that the consumption of meat is often associated with masculinity [40]. Therefore, there is a need for social change, in which concern for the environment is not something that is exclusive to just females [45]. PhD students' responses are, in the majority, from male, being also male students that frequent the canteen the most and likewise does not consider changes in their diet when it comes to meat.…”
Section: Discussion On the Awareness And Willingness To Reduce Meat Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las revisiones sistemáticas cuentan con gran legitimidad y desarrollo en las ciencias médicas, aunque durante las últimas décadas se han desarrollado importantes esfuerzos para otros ámbitos de investigación (Popay et al, 2006). En las Ciencias Sociales, su desarrollo ha implicado una adaptación de los criterios originales y la creación de nuevos protocolos, como la declaración PRISMA 4 , que permite desarrollar un paso a paso estandarizado que mejora la calidad de la búsqueda y sistematización de la información, bajo los principios de transparencia, replicabilidad y actualización (García-Vinuesa et al, 2020;Rethlefsen et al, 2021).…”
Section: Metodologíaunclassified
“…This fact may be explained, like in other environmental areas, by their motivation to conservation initiatives. Furthermore, in global issues like climate change, women are more concerned about the problem, and show greater ecocentric willingness to accept measures to address it [46].…”
Section: Communicationmentioning
confidence: 99%